2008
DOI: 10.1182/blood.v112.11.3455.3455
|View full text |Cite
|
Sign up to set email alerts
|

A Transgenic Mouse Model for Congenital Dyserythropoietic Anemia Type I

Abstract: The Congenital Dyseyrthropoetic Anemias (CDA) are a heterogeneous group of inborn defects characterized by anemia of varying severity and morphological abnormalities of bone marrow erythroblasts. Studying their pathology has the potential to contribute to the understanding of the normal process of erythropoiesis. In CDA type I, the phenotype is largely limited to the red cell lineage with erythroblasts showing characteristic spongy nuclear chromatin on electron microscopy. Its genetic basis is due to missense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…66 For CDAI, the only Cdan1 transgenic mouse model created to date has shown embryonic lethality. 67 For the C15ORF41 gene, 2 cellular models have been created: 1 in human umbilical-derived erythroid precursor (HUDEP)-2 cells using CRISPR/CAS9 technology, 68 and the other in K562 cells through overexpression of the H230P and Y94S mutations. 10 The model in the HUDEP-2 cells remains to be investigated, whereas the K562 models showed impaired erythroid differentiation.…”
Section: Cellular and Animal Models Of Cdasmentioning
confidence: 99%
“…66 For CDAI, the only Cdan1 transgenic mouse model created to date has shown embryonic lethality. 67 For the C15ORF41 gene, 2 cellular models have been created: 1 in human umbilical-derived erythroid precursor (HUDEP)-2 cells using CRISPR/CAS9 technology, 68 and the other in K562 cells through overexpression of the H230P and Y94S mutations. 10 The model in the HUDEP-2 cells remains to be investigated, whereas the K562 models showed impaired erythroid differentiation.…”
Section: Cellular and Animal Models Of Cdasmentioning
confidence: 99%
“…Interestingly, CDIN1 is homologous to restriction endonucleases and a high throughput protein interaction survey has indicated that it interacts with ASF1B [20,25], adding to the hypothesis that DNA replication and chromatin assembly are hampered in CDA 1. Cdan1 knockout mice die at an early embryonic stage of development (E6.5) [26]. There is no information on Cdin1 knockout mice in the literature, but The International Mouse Phenotyping Consortium (www.mousephenotype.org) lists the homozygous Cdin1 em1(IMPC)J allele as lethal at embryonic day 9.5.…”
mentioning
confidence: 99%